Peningkatan Kapabilitas Kinerja untuk Meningkatkan Mutu dan Pelayanan di Auraderma - Puji Setya Sunarka; Deewar Mahesa; Sukardi Sukardi; Fika Ulfa Widiwati (Universitas Maritim AMNI Semarang, 2024)
The service program carried out at the Auradherma company which operates in the field of beauty clinic services, the aim to be achieved in this service activity is to provide motivation and direction related to improving employee performance, this activity was attended by all Auradherma employees totaling 50 participants from various work departments which is in Auradherma. Organizational performance is highly dependent on the quality of human resources, and employee performance is influenced by understanding Standard Operating Procedures (SOP) and accurate performance assessments. It is hoped that this service program can have a significant impact on improving employee performance by prioritizing quality and service amidst competition in the beauty business which is currently developing in several regions and is one of the components of society's current needs.